Patient Perceptions of COVID-19-Related Surgical Delay: An Analysis of Patients Awaiting Total Hip and Knee Arthroplasty. (November 2020) - Wilson, Jacob M.; Schwartz, Andrew M.; Grissom, Helyn E.; Holmes, Jeffrey S.; Farley, Kevin X.; Bradbury, Thomas L.; Guild, George N.
Background: COVID-19 has caused unprecedented delays in elective orthopedic surgery. Understanding patients' perceptions of the disruptions in care and their willingness to reengage the healthcare system are crucial to planning the resumption of elective care. Questions/Purposes: The purpose of this study was to elicit patient perceptions about delays in total joint arthroplasty during the COVID-19 pandemic. Methods: We identified a consecutive series of patients who experienced COVID-19-driven delays to scheduled total hip or knee arthroplasty at an urban, academic medical center in the Southeastern United States. A 20-item survey was administered via telephone. Answers were recorded and descriptive statistics were performed. A post hoc χ -square analysis compared characteristics and outlooks of patients who did and did not immediately desire surgery. Results: Of 111 patients (64% of those identified) who met inclusion criteria and completed the survey, 96% said they felt that they were treated fairly and 90% said that the surgical delay was in their best interest; 68% reported emotional distress from the delay, but 45% reported a desire to wait longer for the pandemic to subside. Lower joint-function scores, higher pain levels, higher pain catastrophizing scores, and longer latency from personally deciding to pursue surgery were associated with the reported need for immediate surgery. Conclusion: Overall, patients reported that they understood the need for elective surgical delays during the COVID-19 pandemic. However, the psychological implications they reported were not negligible. Patient preference for immediate reengagement with the healthcare system was dichotomous, with many patients favoring precautionarily furthering the delay. Understanding these preferences will help optimize elective orthopedic care during unprecedented times.